Analisis Framing Dalam Pemberitaan Politik Di tvonenews.com : Studi Kasus Pemilihan Presiden 2024 - Pangeran Siagian; Mara Untung Ritonga (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to describe the framing of the 2024 presidential election news on tvonenews.com and explain the interpretation of the 2024 presidential election news on tvonenews.com. The research method uses descriptive analysis with Pan and Kosicki's framing analysis approach. The main data used comes from political news published in the media tvonenews.com in the period 14 November 2023-14 January 2024. Then the data was analyzed using Zhongdang Pan and Gerald M. Kosicki's framing analysis using four analytical structures, namely syntax, script, thematic , and rhetorical. To explain the interpretation of the news, the author uses Van Djik's critical discourse analysis with analysis of social cognition and social context. The results of the research show that Pan and Kosicki's framing analysis revealed that the news framing presented by tvonenews.com was unbalanced and in favor of one of the partners, which could influence people's attitudes and provide different interpretations in society.